Faktor - Faktor Yang Berhubungan Dengan Kejadian Guillain-Barré Syndrome (GBS) : Literatur Review - Aulia Nur Fadilah; Fitriyani, Fitriyani; Suharmanto, Suharmanto (CV. Jasa Sukses Abadi, 2025)
Guillain-Barré Syndrome (GBS) is an acute neurological disease characterized by progressive muscle weakness, accompanied by decreased or loss of reflexes due to an autoimmune process that attacks the peripheral nervous system. This condition can progress rapidly and potentially lead to paralysis and even respiratory failure if not treated promptly. This literature review aims to identify and analyze factors associated with the occurrence of Guillain-Barré Syndrome based on recent research. The research method was conducted through a literature review using Google Scholar and PubMed databases using the keywords